Vater - Land - Liebe. Usus, Abusus und Habitus in Catherine Bernards ‚Brutus' - Steigerwald, Jörn (Artes. Zeitschrift für Literatur und Künste der frühmodernen Welt)

Context-specific adaptation for head fakes in basketball: a study on player-specific fake-frequency schedules - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Giesen, Carina G.; Rothermund, Klaus; Weigelt, Matthias (Abstractband des 56. Herbsttreffens experimentelle Kognitionspsychologie (HexKop))

»Faszination und Gewalt: Musik in der NS-Zeit.« Vortrag zur Eröffnung des Jahres der Christlich-Jüdischen Zusammenarbeit 2024 - Grotjahn, Rebecca

»Wir wollen niemals auseinandergehn«: Zur Trennungsgeschichte von Belcanto und Popgesang im 20. Jahrhundert - Grotjahn, Rebecca (Musik erleben – erforschen – vermitteln. Begegnungen mit Thomas Krettenauer)

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Beule, Felix; Sander, Sascha; Meschut, Gerson; Damm, Jannis; Kasper, Yann; Albiez, Matthias; Kötz, Fabian; Matzenmiller, Anton (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

»Tragik des Augenblicks. Zu Arno Lückers »250 Komponistinnen. Frauen schreiben Musikgeschichte« - Grotjahn, Rebecca (kontrovers)

„Stammtisch Austausch E-Lehre“ für Lehrende an Schulen und Hochschulen - Neiske, Iris; Stroop, Dietlinde (Lehrkräftebildung in der digitalen Welt. Zukunftsorientierte Forschungs- und Praxisperspektiven)
In einer Welt, die von Digitalisierung geprägt ist, hat sich die Bildungslandschaft verändert, wodurch die Notwendigkeit für E-Learning und digitale Lehrmethoden in Schulen und Hochschulen offensichtlich wurde. Dieser Artikel beschreibt die Einführung eines niederschwelligen Weiterbildungsangebots, des „Stammtisch Austausch E-Lehre“, in Paderborn. Das Ziel dieses Angebots ist es, Lehrende aus verschiedenen Bildungseinrichtungen zu vernetzen und ihnen die Möglichkeit zu geben, innovative digitale Lernszenarien und E-Learning-Konzepte kennenzulernen. Dies geschieht in Form von kurzen, kostenlosen Fortbildungseinheiten. Die Veranstaltungen bieten Raum für den Austausch über medienpädagogische und didaktische Entwicklungen, den Einsatz digitaler Tools und die Integration digitaler Medien in Unterricht und Lehre. Die Zielgruppe umfasst Lehrkräfte aus Schulen in Ostwestfalen-Lippe (OWL) sowie Universitätslehrende der Universität Paderborn. Durch das offene Fortbildungsformat und die Möglichkeit zum kollegialen Austausch in entspannter Atmosphäre trägt der „Stammtisch Austausch E-Lehre“ dazu bei, die digitale Bildung in der Region zu fördern und eine Brücke zwischen Schul- und Hochschulwelt zu schlagen.

Hochschullehre postdigital

Ressourcennutzung von Schüler:innen zum Lernen von Mathematik - Stallmeister, Lea; Rezat, Sebastian (Beiträge zum Mathematikunterricht 2024 - 57. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

A Quantum Pulse Gate Enhanced Photonic Radar Architecture - Kruse, Stephan; Brecht, Benjamin; Silberhorn, Christine

Hybrid modeling of multibody systems: Comparison of two discrepancy models for trajectory prediction - Wohlleben, Meike Claudia; Röder, Benedict; Ebel, Henrik; Muth, Lars; Sextro, Walter; Eberhard, Peter (PAMM)
Abstract This study focuses on hybrid modeling approaches that combine physical and data-driven methods to create more effective dynamical system models. In particular, it examines discrepancy models, a type of hybrid model that integrates a physical system model with data-driven compensation for inaccuracies. The study applies two discrepancy modeling methods to a multibody system using discrepancies in the state vector and its time derivative, respectively. As an application example, a four-bar linkage with nonlinear damping is investigated, using a simplified conservative system as a physical model. The comparative analysis of the two methods shows that the continuous approach generally outperforms the discrete method in terms of accuracy and computational efficiency, especially for velocity prediction and prediction horizon. However, scenarios, where input signals for training and testing differ, present nuanced findings. When the continuous method is trained on complex signals (sine) and tested on simpler ones (stair), it struggles to deliver satisfactory results, exhibiting notably higher root mean square error (RMSE) values, particularly in angular velocity prediction. Conversely, training on simple signals (stair) and testing on complex ones (sine) surprisingly yields low RMSE values, indicating the continuous method’s adaptability. While the discrete method aligns more closely with expectations and performs better in certain scenarios, its results are consistently moderate, neither exceptional nor particularly poor. The study also introduces a selection framework for choosing the most suitable algorithm based on the specific characteristics of the modeling task. This framework provides guidance for researchers and practitioners in leveraging hybrid modeling effectively. Finally, the study concludes with an outlook on future research directions.

Weighted school choice problems and the weighted top trading cycles mechanism - Stroh-Maraun, Nadja (Mathematical Social Sciences)
There are a number of school choice problems in which students are heterogeneous according to the number of seats they occupy at the school they are assigned to. We propose a weighted school choice problem by assigning each student a so-called weight and formulate the weighted top trading cycles algorithm (WTTC) to find a matching. The WTTC is strategy-proof and results in a Pareto efficient matching. While the WTTC is a robust extension of the TTC when weights are introduced, it is no longer guaranteed that each student gets a seat at a school even if the overall capacity exceeds the sum of weights. Additionally, the WTTC introduces a trade-off between weights and priorities as a student with a higher weight has a disadvantage to be matched to a particular school compared to a student with the same schools’ priorities but a smaller weight.
Keywords: Matching; School choice; College admission problems; Top trading cycles; Pareto efficiency; Strategy-proofness

An additive approach toward determination of liquid-phase mass transfer coefficients in sandwich packings - Franke, Patrick; Schlattmann, Ulrich; Devasthali, Oorv; Lutters, Nicole; Schubert, Markus; Hampel, Uwe; Iliuta, Ion; Larachi, Faïçal; Kenig, Eugeny (Chemical Engineering Science)

Teachers and trainers in dual vocational training as change agents for sustainable development!? – Questions on the professionalisation of in-company trainers and vocational school teachers - Hantke, Harald; Kiepe, Karina (Sustainability in Vocational Education and Training – National and International Experiences)

Pilot projects: Phenomena and key points of transfer of vocational education and training for sustainable development (VETSD) - Schlömer, Tobias; Kiepe, Karina; Rüdebusch, Gerrit; Günther, Niklas; Lieht, Jennifer (Sustainability in Vocational Education and Training – National and International Experiences)

Betriebliche Ausbilder:innen als Change Agents einer BBNE – Analyse und Reflexion im Spiegel der Ausbilderforschung - Schlömer, Tobias; Kiepe, Karina (Betriebliches Aus- und Weiterbildungspersonal im Fokus der Berufsbildungsforschung)

AnnoPy. Fachspezifische wissenschaftliche Textkompetenzen mit digitalen Medien in der Lehre fördern - Rezat, Sebastian; Rezat, Sara; Scholle, Oliver; Schulte, Carsten; Winkelnkemper, Felix (Lehrkräftebildung in der digitalen Welt. Zukunftsorientierte Forschungs- und Praxisperspektiven)
AnnoPy ist ein digitales Werkzeug, das an der Universität Paderborn in einer interdisziplinären Kooperation zwischen der Germanistischen Sprachdidaktik, Mathematikdidaktik und Informatikdidaktik entwickelt wurde, um wissenschaftliche Textkompetenzen zu fördern. Es kann in Präsenz- oder Blended-Learning-Szenarien eingesetzt werden, um eine Brücke zwischen individueller Auseinandersetzung mit dem Text und dessen sozial-diskursiver Aushandlung zu schlagen. Im Beitrag werden unterschiedliche Einsatzszenarien aus den drei beteiligten Disziplinen exemplarisch dargestellt, die jeweils unterschiedliche Facetten wissenschaftlicher Textkompetenz in den Mittelpunkt stellen. Im Fokus stehen dabei insbesondere die Förderung fachspezifischer Lesekompetenz im Rahmen einer Vorlesung mit großen Teilnehmendenzahlen sowie die Anwendung fachspezifischer Theorien und Konzepte in der Erschließung, Analyse und Beurteilung von Texten.
Keywords: digitale Medien; wissenschaftliche Textkompetenz; Lehrkonzept

Qualitative Analysis and Promotion the Language Acquisition of International Students at Universities in Germany: Opportunities and Challenges - Beutner, Marc; Lindenthal, Helene Maja; Lüttke, Jan-Phillip (Open Access Journal of Education & Language Studies)

Inter- and intragenerational differences in corrupt behavior: The development of morals after German reunification - Auer, Thorsten Fabian; Berg, Timo; Hoffmann, Christin (European Journal of Comparative Economics)
We investigate differences in bribing decisions among two generations from East and West Germany in a bribery game conducted as an online study (N=168). This way, we aim to explore moral considerations of individuals influenced by two formerly different institutional systems. We find a higher propensity to bribe among young Germans compared to the older generation. Young East Germans even reveal a slightly greater inclination to bribe than their West German counterparts. We conclude that preferences for personal favors may be induced among young East Germans given the tense relationship between market opportunities and conveyed cultural traits of a socialist imprint.
Keywords: Moral behavior; Corruption; Intra- and intergenerational study; Institutional transformation; Reunification

Liebestragödie. Genealogien einer französischen Gattung des 17. Jahrhunderts - Schlieper, Hendrik